Floristic study of the southern bunchgrass paramos of Ecuador - Izco, Jesús (2007)
A study of the flora of the bunchgrass paramo with antropic origin of different mountain ranges from the Andean areas in southern Ecuador (provinces of Azuay and Loja) was conducted. The study areas range between the 2850 m and 3635 m of altitude. The local flora is composed by 43 families, 120 genera and 216 species of vascular plants; this particular flora is compared with that of other Andean bunchgrass paramos, the floristic richness of genus and species is studied by altitudinal levels (100 m), and the characteristic flora of each level of the area is established. Finally the biogeographic aspects of the flora are discussed.